Dual-Purpose Mine Land Rehabilitation: Integrating Environmental Restoration and Sustainable Use for Tourism and Agriculture in Cajamarca - SME Annual Meeting 2025 - M. Mendoza; F. Ysla (Society for Mining, Metallurgy & Exploration, 2025)
This proposal, based on the CIEMAN Cajamarca - Hualgayoc initiative, focuses on “Transforming Abandoned Mine Lands’’ We aim to study and assess the feasibility of an innovative rehabilitation method. Contaminated soils will be moved from the upper to the lower site, encapsulated with geosynthetic barriers, and covered with topsoil. The decontaminated upper area will be used for planting trees and large-stemmed plants for hiking and tourism, while the lower encapsulated area will support livestock and short- stemmed crops. This study will evaluate the economic viability and multi-use potential of this technique, promoting sustainable land recovery in Cajamarca, Peru.